Our founders - Chief Editor (Annals of Arid Zone, 2024)
Born on December 17, 1931, in Mathura, Uttar Pradesh, Dr. Ishwar Prakash embarked on an illustrious journey marked by remarkable achievements in the field of zoology. He graduated from Rajasthan University, Jaipur, in Biology followed by a Master’s degree in Zoology. His academic prowess Dr. Ishwar Prakash (1931-2002) was further exemplified by the attainment of a Ph.D. degree from the same university in 1957. He distinguished himself as an eminent mammal expert, particularly renowned for his expertise in rodent studies in very early stages of his career. His seminal contributions in this domain were recognized with the award of a D.Sc. degree in 1983, a distinction making him the first researcher from Rajasthan to achieve this honour. He joined the Central Arid Zone Research Institute in 1961and dedicated three decades of his life to advancing rodent research. Under his visionary leadership, ICAR-CAZRI India Coordinated Rodent Research Project (AICRP) from 1977 to 1982, demonstrating his commitment to collaborative scientific endeavours. Acknowledging his exceptional contributions, the Indian Council of Agricultural Research bestowed upon him the esteemed title of Professor of Eminence in 1980, a position he held until his retirement in 1991. Even after stepping down from official duties, Dr. Ishwar Prakash continued to pursue his passion for research. Recognized as a Senior Scientist by the Indian National Science Council, he spearheaded significant research projects focusing on the study of small mammals in the Aravalli range. Witnessed unprecedented growth in rodent research, culminating in the establishment of a world-class rodent research laboratory. Notably, he played a pivotal role as the founding Project Coordinator of the All Dr. Ishwar Prakash’s scholarly legacy is immortalized through his extensive body of work, comprising over 350 research papers and more than 20 influential books that remain seminal in the realm of desert ecology. His intellectual prowess continues to inspire the scientific community, underscoring his enduring impact on the field. Though he departed from this world on May 14, 2002 his invaluable contributions and remarkable talent still inspire the scientists